Observing Music Therapy in Dementia: Repeated Single-case Studies Assessing Well-being and Sociable Interaction. Issue 4 (8th August 2022) - Madsø, Kristine Gustavsen; Molde, Helge; Hynninen, Kia Minna; Nordhus, Inger Hilde
ABSTRACT: Objectives: This study compared behavioral expressions of momentary well-being and sociable behavior toward significant others during music therapy and regular social interaction. Methods: A 10-week active music therapy intervention was provided for people living with dementia and family caregivers. A bi-phasic AB single-case design was replicated for three sessions per dyad and coded using the Observable Well-being in Living with Dementia-Scale (OWLS) and the Verbal and Nonverbal Sociable Interaction Scale-Care Receiver (VNVIS-CR). Effect sizes (Log Response Ratio) were calculated for each session and analyzed with robust cluster meta-analysis. Results: Eleven dyads were included, and 32 sessions analyzed (2102 observations). Within sessions we found a 48% increase in well-being, and a 32% increase in sociable interaction during music therapy. Heterogeneity was high. Dementia severity predicted an increase in nonverbal sociable interaction (93% for moderate dementia). Depression and time did not predict any change. Conclusion: The potential of music therapy to increase well-being and sociable interactions toward significant others calls for further investigation of heterogeneity and covariates. Single-case designs are demonstrated to be feasible for these investigations. Clinical implications: Preference-based music therapy may alleviate some of the individual and relational consequences of living with dementia, facilitating positive emotions and connection to significant others.